ImageSubXSS: an image substitute technique to prevent Cross-Site Scripting attacks - PMD Nagarjun; Shaik Shakeel Ahamad (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Cross-Site Scripting (XSS) is one of serious web application attack. Web applications are involved in every activity of human life. JavaScript plays a major role in these web applications. In XSS attacks hacker inject malicious JavaScript into a trusted web application, execution of that malicious script may steal sensitive information from the user. Previous solutions to prevent XSS attacks require a lot of effort to integrate into existing web applications, some solutions works at client-side and some solutions works based on filter list which needs to be updated regularly. In this paper, we propose an Image Substitute technique (ImageSubXSS) to prevent Cross-Site Scripting attacks which works at the server-side. The proposed solution is implemented and evaluated on a number of XSS attacks. With a single line, developers can integrate ImageSubXSS into their applications and the proposed solution is able to prevent XSS attacks effectively.